ANALISIS TITIK IMPAS PADA INDUSTRI ROTAN HIDAYAH SIDOREJO KECAMATAN CURUP TENGAH - Retno Wulandari (Politeknik Raflesia Press, 2020)
Good profit planning will affect the success of the business in achieving optimal profit. The calculation of future profits is very useful for preparing the profit planning process. In general, almost all management decisions will have more impact on activities or attitudes in the future than on past activities or attitudes. Thus management decision making is a continuous process. This continuous process makes management must be able to anticipate upcoming events and plan what must be done, including planning company profits. Profit Volume Cost Analysis (cost-volume-profit analiysis) is often called a break event point analysis because of the significance of the break event point in this analysis, in the profit volume cost analysis, volume refers to all activity cost triggers, such as sales units are assumed to collaborate with changes in income, costs and profits. Based on the results of the analysis, it can be concluded as follows; The amount of break even points for living room chair products in Hidayah Sidorejo's rattan industry is 4 units, meaning that the company will be in a position where the profit is equal to 0. The amount of contribution margin for living room chair products in Hidayah Sidorejo's rattan industry is Rp. . 2,879,000 The operating profit target is assumed if Hidayah's rattan industry is targeting a profit of Rp. 10,000,000, then the number of units that must be sold is 7 units of living room chairs. The results of the cost volume profit analysis in the decision making for advertising spending show that Hidayah's rattan industry decides to advertise in the newspaper with an advertising cost of Rp. 1000,000, then this will increase the contribution margin by Rp. 2,879,000 and operating profit increased to Rp. 1,879,000 even though the cost continued to increase to Rp. 11,000,000 The results of the cost volume profit analysis in decision making to reduce the selling price from Rp. 6000,000 / chair set becomes Rp. 5,000,000 / set of chairs will reduce the contribution margin by Rp. 10,000,000, although if you lower the selling price the sales will increase to 10 units.